Extracellular polymeric substances in Antarctic environments: A review of their ecological roles and impact on glacier biogeochemical cycles - Nagar, Shipra; Antony, Runa; Thamban, Meloth (Polar Science, 2021)
Antarctic continent comprises diverse ecosystems like snow, glacier ice, sea ice, melt pools, glacial soils, supraglacial and subglacial lakes that accommodate numerous microbial and algal communities. These biotic groups secrete matrices of biomacromolecules called Extracellular Polymeric Substances (EPSs), which enhance their ability to withstand extreme environmental conditions. EPSs are mainly composed of exopolysaccharides, proteins, lipids and nucleic acids, and exhibit assorted activities due to diverse functionalities of matrix like spatial conformation, molecular weight, rheology, charge, size and affinity. Several protective and ecological functions such as cryoprotection, anti-desiccation, buffering against high salinity and pH, trace metal uptake and binding, sequestration of dissolved organic matter and nutrients, aggregate formation and biofilm production have been attributed to microbial EPSs. They also contribute to production of dissolved and particulate organic matter and hence can influence biogeochemical cycling of elements, especially carbon and iron. Further, they aid in aggregation of dust particles on the glacier surface, substantially reducing the albedo of the ice and thereby accelerate melting of glaciers. This study provides an overview of role of EPSs in Antarctic ecosystems, its ecological significance and chemical functionalities, and discusses the approach for a better understanding of relevance of EPSs in biogeochemistry of Antarctic environments. journal article